Food worker program related to overweight and obesity: a systematic review - Chaves, Muriel de Jesus (2013)
Obesity is now recognized as a major public health problem, affecting populations with different socioeconomic levels, gender, age. Social programs such as PAT (Workers' Food Program) are created with the aim of improving the nutritional status of workers. Thus, the objective was to demonstrate through a systematic review ofthe Workers' Food Program related to overweight and obesity. We reviewed twenty national surveys, between the years 2002 to 2010. The descriptors used for the search were the Workers' Food Program, Food workers, Nutritional Status of Workers in the database of the Scientific Electronic Library Online (SciELO). With the nutritional transition, cases of overweight stands out as a public health problem. Diabetes and hypertension were observed in studies with workers who have the PAT as a benefit. Thus, it appears that the program can not reflect positively on improving the quality of life of workers, reflecting the framework of overweight. The program needs to be revised and adapted to current conditions of the nutritional transition.